Improving supply chain performance through enhanced information sharing using an EDI cloud service - Enhörning, Oskar; Östman, Bill (My University, 2015)
Pagero is a company primarily providing scalable services for exchange of financial messages using the cloud service Pagero Online, which allows actors to connect regardless of ERP-system or message formatting used. Both the industry and Pagero have grown rapidly during the last couple of years, Pagero constantly develops new message types and services to include in the current repertoire. Pagero’s by far most important message is currently the e-invoice. Instead of utilising peer-to-peer connections, all traffic is directed through the cloud and converted to whichever format is requested by the recipient. The rise of this project lies in the perception that the data stored in Pagero Online holds untapped potential for providing additional benefits to Pagero’s clients and thereby increasing Pagero’s competitiveness. This project brings knowledge to a field not yet explored by Pagero; how the current cloud-system Pagero Online can be used to identify, and contribute to, the increase of clients’ supply chain performance by enabling enhanced information sharing. A method for identifying high potential clients in Pagero Online has been devised and used to select a case organisation which has been studied in order to confirm the existence of improvement potential. How Pagero can help the case organisation to reach the improved performance identified in the case study, and how to repeat the process with further clients has been analysed and a final recommendation to Pagero is made. This project concludes that Pagero can contribute to the increase of clients’ performance, to be able to do it effectively in the future, further knowledge about clients’ industries and processes must be acquired.
Keywords: Transport; Övrig industriell teknik och ekonomi; Transport; Other industrial engineering and economics